Odpowiedzi

2009-10-26T15:35:24+01:00
A.
1/4x²+2x+4
b.
3(16y²- 56y+49)= 48y²-168y + 147
c.
4 (x² - 1)= 4x² - 4
d.
15(9x²+12x+4)= 135x² + 180x +60
2009-10-26T15:54:14+01:00
A) (1/2x + 2)²= ¼x² + 2x + 4
b) 3(4y - 7)²= 3(16y² - 56y + 49)= 48y² - 168y + 147
c)4(x-1)(x+1)= 4(x² - 1)= 4x² - 4
d)15(3x+2)²= 15( 9x² + 12x + 4)= 135x² + 170x + 60
2009-10-26T16:01:30+01:00
A) (1/2x + 2)²= (1/2x)² + 2 * 1/2x * 2 + (2)² = 1/4x² + 2x +4
b) 3(4y - 7)²= 3 [(4y)² - 2 * 4y * 7 - (7)²] = 3(16y² - 56y - 49)= 48y² - 168y + 147
c) 4(x-1)(x+1)= 4(x²-1) = 4x² -4
d) 15(3x+2)² = 15[(3x)² + 2 * 3x *2 + (2)² =15(9x² + 12x +4)= 135x²+ 180x + 60